Real-World Functioning in Patients With Schizophrenia: Beyond Negative and Cognitive Symptoms - García-Portilla, María Paz; García-Álvarez, Leticia; González-Blanco, Leticia; Dal Santo, Francesco; Bobes-Bascarán, Teresa; Martínez-Cao, Clara; García-Fernández, Ainoa; Sáiz, Pilar A.; Bobes, Julio (Frontiers in Psychiatry, 2021)
Interest in the idea of recovery for certain patients with schizophrenia has been growing over the last decade. Improving symptomatology and functioning is crucial for achieving this. Our study aims to identify those factors that substantially contribute to real-world functioning in these patients. We carried out a cross-sectional study in stable outpatients with schizophrenia on maintenance antipsychotic monotherapy. Patients: We studied 144 outpatients with schizophrenia (DSM-IV-TR criteria) meeting the following criteria: 1) 18-65 years of age; 2) being clinically stable for at least the previous three months; 3) on maintenance antipsychotic monotherapy (prescriptions ≤ 10 mg olanzapine, ≤ 200 mg quetiapine, or ≤ 100 mg levomepromazine as hypnotics were also allowed); 4) written informed consent. Assessment: We collected information on demographic and clinical variables by using an ad hoc questionnaire. For psychopathology, we employed the Spanish versions of the following psychometric instruments: the Positive and Negative Syndrome Scale (PANSS), the Brief Negative Symptom Scale (BNSS-Sp), and the Calgary Depression Scale (CDS). In addition, cognitive domains were assessed using the Verbal Fluency Test (VFT), the Digit Symbol Substitution Test (DSST), and the Trail Making Test, parts A and B (TMT-A and TMT-B). Finally, we employed the Spanish versions of the University of California San Diego Performance-based Skills Assessment (Sp-UPSA) and the Personal and Social Performance (PSP) for assessing functional capacity and real-world functioning, respectively. Statistical analysis: A forward stepwise regression was conducted by entering those variables significantly associated with PSP total score into the univariate analyses (Student’s t-test, ANOVA with Duncan’s post hoc test, or bivariate Pearson correlation). A total of 144 patients; mean age 40 years, 64% males, mean length of illness 12.4 years, PSP total score 54.3. The final model was a significant predictor of real-world functioning [F(7,131) = 36.371, p < 0.001] and explained 66.0% of the variance. Variables retained in the model: BNSS-Sp abulia, asociality, and blunted affect, PANSS general psychopathology, Sp-UPSA transportation, TMT-B, and heart rate. Our model will contribute to a more efficient and personalized daily clinical practice by assigning specific interventions to each patient based on specific impaired factors in order to improve functioning.